Construction and application of highly sensitive spinel nanocrystalline zinc chromite decorated multiwalled carbon nanotube modified carbon paste electrode (ZnCr2O4@MWCNTs/CPE) for electrochemical determination of alogliptin benzoate in bulk and its dosage form: green chemistry assessment. Issue 30 (30th June 2022) - Attia, Khalid A. M.; Abdel-Monem, Ahmed H.; Ashmawy, Ashraf M.; Eissa, Amr S.; Abdel-Raoof, Ahmed M.
Abstract : A new sensor for alogliptin benzoate (ALG) estimation based on a simple and sensitive method was evolved on multiwalled-carbon-nanotube modified nanocrystalline zinc chromite carbon paste electrodes (ZnCr2 O4 @MWCNTs/CPEs). Abstract : A new sensor for alogliptin benzoate (ALG) estimation based on a simple and sensitive method was evolved on multiwalled-carbon-nanotube modified nanocrystalline zinc chromite carbon paste electrodes (ZnCr2 O4 @MWCNTs/CPEs). ALG electrochemical behavior was evaluated using a cyclic voltammetry (CV), square wave voltammetry (SWV) and chronoamperometry (CA). The new electrode materials were characterized by scanning electron microscope (SEM), transmission electron microscope (TEM), energy dispersive X-ray analysis (EDX) for elemental analysis and mapping, and X-ray diffraction (XRD) and the X-ray photoelectron spectroscopy (XPS) measurements. All these measurements exhibiting enhanced activity and high conductivity compared to the bare electrode without modification. The calibration curves obtained for ALG were in the ranges of 0.1–20 μmol L −1 with a quantification and detection limits of 0.09 and 0.03 μmol L −1, respectively. The prepared sensor showed a good sensitivity and selectivity with less over potential for ALG determination. Finally, the presented method was successfully applied as a simple, precise and selective electrochemical electrode for the estimation of ALG in its pharmaceutical dosage form.